Philosophy and Religion in Abdurrahman Wahid’s Post-Secularism Thought - Walid, Kholid Al; Miri, Mohsen; Norman, Nurul Ain (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2025)
The research aim is to discuss the relationship between philosophy and religion in the thought of Abdurrahman Wahid (Gus Dur), framed within the context of post-secularism. Gus Dur challenges the problem of the rigid dichotomy between philosophy and religion and then encourages an inclusive and dialogical approach through philosophical concepts, consisting of “Pancasila”, “Neo-Modernism and Utilitarianism”, and “Islamic Society”. Gus Dur viewed religion and philosophy as having the potential to mutually enrich and advance social life mutually. The research uses a qualitative method and a philosophical approach to examine how Gus Dur’s thinking can be understood within the framework of post-secularism in the context of Indonesia. This research seeks to illuminate how Gus Dur’s ideas contribute to redefining the relationship between religion and philosophy in the post-secular landscape of Indonesia by bridging spiritual and rational realms. Gus Dur views religion and philosophy not as opposing realms but as two ways of understanding truth. In his view, religion provides meaning and purpose in life, while philosophy offers tools for critical and rational thinking about life’s problems. He rejects secularism, which separates religion from the public sphere and proposes a post-secularism approach that recognizes the role of religion in public life while still respecting the values of rationality.